A natural human monoclonal antibody protects from axonal injury in different CNS degenerative disease models. (February 2018) - Kunbaz, Ahmad; Warrington, Arthur E; Perwein, Maria K; Fereidan-Esfahani, Mahboobeh; Rodriguez, Moses
Axon regeneration after CNS injury is incomplete. This is partially due to the presence of multiple growth inhibitory molecules within myelin that prevent axonal extension. These inhibitors include myelin-associated glycoprotein, Nogo and oligodendrocyte myelin glycoprotein. A natural human recombinant antibody, rHIgM12, was identified by its ability to promote neurite outgrowth in vitro . rHIgM12 overrides the neurite outgrowth inhibition of myelin by binding with high affinity to neuronal PSA-NCAM and gangliosides. This neurite outgrowth is accompanied by increased α-tubulin tyrosination and decreased acetylation which occurs after treatment with rHIgM12. rHIgM12 is efficacious in murine models of human multiple sclerosis and amyotrophic lateral sclerosis, improving axon survival and neurologic function. rHIgM12 has great promise as a therapeutic molecule in a number of CNS disorders characterized by neuronal loss and axonal transection including multiple sclerosis. This review will focus on rHIgM12 discovery, effects in preclinical models and potential applications as a therapeutic reagent for CNS disease.